2019
DOI: 10.1155/2019/2071506
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy and EX-PRESS Implantation in Open-Angle Glaucoma: An Updated Meta-Analysis of Randomized Controlled Trials

Abstract: Purpose Accumulating studies comparing the efficacy and safety of trabeculectomy and EX-PRESS implantation in open-angle glaucoma (OAG) report inconsistent findings. Thus, we conducted the updated meta-analysis to clarify the issue. Methods Randomized controlled trials (RCTs) were selected through search of databases PubMed, Web of Science, Embase, and the Cochrane Library from their inception up until November 2018. The pooled mean difference (MD) for intraocular pressure reduction (IOPR) and antiglaucoma med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Therefore, the search for new informative markers and forecasting methods progression of glaucoma optic neuropathy (GON) is relevant today problem [7,8]. Our previous research has established the effectiveness of the use of trabeculectomy (TE) for the surgical treatment of POAG with implantation of the Ex-Press shunt [9], which coincides with the data of the latter meta-analysis [10].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Therefore, the search for new informative markers and forecasting methods progression of glaucoma optic neuropathy (GON) is relevant today problem [7,8]. Our previous research has established the effectiveness of the use of trabeculectomy (TE) for the surgical treatment of POAG with implantation of the Ex-Press shunt [9], which coincides with the data of the latter meta-analysis [10].…”
Section: Introductionmentioning
confidence: 73%
“…At first glance, this contradicts the classical notion of the importance of high IOP for the development of GON [5]. But it is known that postoperative hypotension has a negative effect on the progression of IOP and excessive reduction of IOP after surgery for POAG worsens the long-term results of surgical treatment [9][10][11]. Our results confirm this opinion -the decrease IOP after surgery has a significant effect on the progression of GON after one year (p = 0.012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Враховуючи дані про зниження ВОТ після хірургічного лікування й негативний вплив післяопераційної гіпотонії [1,8,14] Стадію захворювання визначали за класифікацією периметричних змін глаукоми [1,17]. Пацієнтам виконували трабекулектомію з імплантацією шунта Ex-Press [18]. Операції були виконані під місцевою анестезією однією бригадою хірургів.…”
Section: матеріали та методиunclassified
“…Most trials comparing the efficacy of both procedures, showed equivalent efficacy in heterogeneous groups consisting of phakic and pseudophakic patients [6,7,[10][11][12][13][14][15]. Several meta-analyses comparing Ex-PRESS surgery to standard trabeculectomy showed that the Ex-PRESS surgery is more likely to achieve complete success, with fewer postoperative interventions and possibly a lower frequency of complications such as hypotony [4,16,17].…”
Section: Introductionmentioning
confidence: 99%